2020
DOI: 10.1038/s41438-020-0335-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping and survey of powdery mildew resistance in the wild Central Asian ancestor of cultivated grapevines in Central Asia

Abstract: Cultivated grapevines (Vitis vinifera) lack resistance to powdery mildew (PM) with few exceptions. Resistance to this pathogen within V. vinifera has been reported in earlier studies and identified as the Ren1 locus in two Central Asian table grape accessions. Other PM-resistant cultivated varieties and accessions of the wild ancestor V. vinifera subsp. sylvestris were soon identified raising questions regarding the origin of the resistance. In this study, F1 breeding populations were developed with a PM susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 45 publications
3
37
2
Order By: Relevance
“…However, only an extended phenotypic survey in the same experimental conditions, together with the collected molecular data, could provide clearer insights into the spread of resistance to E. necator in the Caucasian cultivated germplasm. Currently, our genetic ndings are consistent with the Riaz et al [50] study, which identi ed in the same genomic region of chr 13 of a Caucasian V. vinifera subsp. sylvestris a resistance QTL to E. necator.…”
Section: Origin Of the Resistance To E Necator In The Caucasian Grapevinessupporting
confidence: 92%
See 3 more Smart Citations
“…However, only an extended phenotypic survey in the same experimental conditions, together with the collected molecular data, could provide clearer insights into the spread of resistance to E. necator in the Caucasian cultivated germplasm. Currently, our genetic ndings are consistent with the Riaz et al [50] study, which identi ed in the same genomic region of chr 13 of a Caucasian V. vinifera subsp. sylvestris a resistance QTL to E. necator.…”
Section: Origin Of the Resistance To E Necator In The Caucasian Grapevinessupporting
confidence: 92%
“…Our research, in addition to other studies, identi ed the resistance to E. necator in many V. vinifera grapevines of different geographic areas (Caucasus and Central Asia) and collected evidence that its inheritance is shared by wild and cultivated V. vinifera subspecies [18, 19,24,50]. This information and the long history of grapes isolation in the Caucasus region [51,52] suggests that the resistance trait might have been inherited from a V. vinifera progenitor thousands of years ago and conserved in Caucasian cultivars until today.…”
Section: Origin Of the Resistance To E Necator In The Caucasian Grapevinesmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of bioinformatics technology has enabled the development of SSR markers for many species 29 31 . Recently, there have been many reports on SSR development and application 32 38 . These studies have confirmed that SSRs are the classic, popular molecular markers used in plant science.…”
Section: Introductionmentioning
confidence: 99%